Pakistan's agricultural exports, determinants and its potential: an application of stochastic frontier gravity model. Issue 3 (3rd April 2017) - Atif, Rao Muhammad; Haiyun, Liu; Mahmood, Haider
ABSTRACT: The most important and imperative objective of the developing nations is rapid economic growth and exports are generally considered as an engine for economic growth. Being an agro-based economy, agriculture exports play pivotal role not only in economic growth but also in socioeconomic uplifting. This study aims at evaluating main determinants of agricultural exports of Pakistan by applying stochastic frontier gravity model over the period of 1995–2014 for a sample of 63 countries. In addition, the study also analyzes whether there is any untapped export potential between Pakistan and the trading partners in agriculture sector. The results confirm the consistency of gravity model for agriculture exports of Pakistan. Likewise, the estimates also point out that bilateral exchange as well as tariff rates also effect agriculture exports. The study has also incorporated the effect of common border, common culture, colonial history and preferential trading agreements by including their respective dummies. The study confirms the significance of each factor, except common language, with their respective magnitude. Moreover, technical efficiency estimates reveal that Pakistan has great export potential with neighboring, Middle Eastern and European countries.